1996
DOI: 10.1016/0370-2693(95)01433-0
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Λb polarization in Z decays

Abstract: The Λb polarization in hadronic Z decays is measured in semileptonic decays from the average energies of the charged lepton and the neutrino. In a data sample of approximately 3 million hadronic Z decays collected by the ALEPH detector at LEP between 1991 and 1994, 462 +/- 31 Λb candidates are selected using (Λπ+)-lepton correlations. From this event sample, the Λb polarization is measured to be PΛb = -0.23+0.24-0.20(stat.)+0.08-0.07(syst.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 23 publications
0
58
0
1
Order By: Relevance
“…(2.12), all a priori unknown non-perturbative contributions associated with the fragmentation function are contained in D np q→γ (x, µ 0 ) which has to be determined from the data. This non-perturbative input has been extracted from the ALEPH 'photon' + 1 jet data [1] for y cut = 0.06 and z > 0.7. At lowest order, we have [1],…”
Section: Inclusive Photon Production In the Fixed Order Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…(2.12), all a priori unknown non-perturbative contributions associated with the fragmentation function are contained in D np q→γ (x, µ 0 ) which has to be determined from the data. This non-perturbative input has been extracted from the ALEPH 'photon' + 1 jet data [1] for y cut = 0.06 and z > 0.7. At lowest order, we have [1],…”
Section: Inclusive Photon Production In the Fixed Order Approachmentioning
confidence: 99%
“…These events were defined by the application of the Durham jet clustering algorithm [4] to both hadronic and electromagnetic clusters. A comparison between the observed rate and the O(α) [1,5] or O(αα s ) [6] theoretical estimates yielded a first determination of the quark-to-photon fragmentation function accurate at leading and next-to-leading order. The theoretical basis on which the measurement of the 'photon' + 1 jet rate relies, is an explicit counting of powers of the strong coupling α s in both the direct and the fragmentation contributions, and where no resummation of ln µ 2 F is performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is shown in [46] that additional requirements on a muon from the b-jet is capable of improving both the tagging and the tagging-overmistag efficiencies for b-quarks up to intermediate jet p T while no information is available for very energetic jets. Regarding the b-hadron helicity, there is no result currently available at the LHC, thus we take the values available from LEP [18,19], quantifiable in an overall 10% efficiency, as an estimate to quantitatively discuss spin observables. By considering this extra efficiency factor, we are in fact also further selecting b-jets with prompt hard leptons.…”
Section: Efficiencies and Uncertaintiesmentioning
confidence: 99%
“…If the b-quark hadronises before decaying, it has also been shown that its spin informations can be transmitted to b-hadrons (e.g., Λ b ), albeit with some dilution factors [18]. Then, the semi-leptonic decays of the latter would enable spin measurements, as pioneered at LEP [19]. It is not clear however if the same measurement is possible at the LHC, due to the higher boost of the emerging lepton and the narrower b-jet cone.…”
Section: Introductionmentioning
confidence: 99%